2023
DOI: 10.1021/acs.jpca.2c06601
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Flame Synthesis of LaFexCo1–xO3 (x = 0.2, 0.3) Perovskite Nanoparticles for Oxygen Evolution Reaction in Water Splitting: Effect of Precursor Chemistry (Acetates and Nitrates)

Abstract: The product properties of mixed oxide nanoparticles generated via spray-flame synthesis depend on an intricate interplay of solvent and precursor chemistries in the processed solution. The effect of two different sets of metal precursors, acetates and nitrates, dissolved in a mixture of ethanol (35 Vol.%) and 2-ethylhexanoic acid (2-EHA, 65 Vol.%) was investigated for the synthesis of LaFe x Co 1−x O 3 (x = 0.2, 0.3) perovskites. Regardless of the set of precursors, similar particle-size distributions (d p = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…Flame synthesis offers possible routes for forming a wide variety of materials of utility in the energy transition. Angel et al explored the effect of different precursors on the spray-flame synthesis of LaFe x Co 1– x O 3 perovskite nanoparticles with characterizations via transmission electron microscopy, energy dispersive X-ray mappings, Fourier-transform infrared, Brunauer, Emmett, Teller, Mössbauer, and X-ray photoelectron spectroscopies . The samples obtained were also tested for their effectiveness as catalysts for the oxygen evolution reaction in water splitting .…”
Section: Systems and Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Flame synthesis offers possible routes for forming a wide variety of materials of utility in the energy transition. Angel et al explored the effect of different precursors on the spray-flame synthesis of LaFe x Co 1– x O 3 perovskite nanoparticles with characterizations via transmission electron microscopy, energy dispersive X-ray mappings, Fourier-transform infrared, Brunauer, Emmett, Teller, Mössbauer, and X-ray photoelectron spectroscopies . The samples obtained were also tested for their effectiveness as catalysts for the oxygen evolution reaction in water splitting .…”
Section: Systems and Processesmentioning
confidence: 99%
“…Angel et al explored the effect of different precursors on the spray-flame synthesis of LaFe x Co 1−x O 3 perovskite nanoparticles with characterizations via transmission electron microscopy, energy dispersive X-ray mappings, Fourier-transform infrared, Brunauer, Emmett, Teller, Mossbauer, and X-ray photoelectron spectroscopies. 48 The samples obtained were also tested for their effectiveness as catalysts for the oxygen evolution reaction in water splitting. 48 These and other thermochemical conversion processes can benefit from decades of combustion research to improve their efficiency, selectivity, and emission signature.…”
Section: ■ Molecules and Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tausende Quadratkilometer Elektroden lassen sich nur im Schulterschluss zwischen den Natur-und Ingenieurwissenschaften realisieren, etwa durch die Entwicklung skalierbarer Syntheseverfahren sowie kontinuierlicher und automatisierter Sprühbeschichtungs-und Rolle-zu-Rolle-Prozesse. 24,25) Da es sich bei Elektrokatalysatoren häufig um Nanomaterialien handelt, sind funktionale Partikel im Sub-µm-Bereich herzustellen und zu handhaben. Dazu gehört die für die Beschichtung und Trocknung nötige Kolloidverfahrenstechnik, die gleichzeitig angegangen werden muss.…”
Section: Skalierbarkeitunclassified
“…In addition, vapor phase methods of LFO bulk synthesis were reported that utilize spray−flame pyrolysis. 14 The sonication methods are promising alternatives to conventional methods due to its decreased time and energy requirements. 15 However, the utilization of complex and energy-intensive reagents in mainstream synthesis methods have influenced researchers in the direction of "green synthesis".…”
Section: ■ Introductionmentioning
confidence: 99%